2000
DOI: 10.2460/ajvr.2000.61.1309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-methylindole production and immunity against bovine respiratory syncytial virus on development of respiratory tract disease and rate of gain of feedlot cattle

Abstract: Results suggest that abrogating the effects of 3MI and BRSV infection may improve the health and growth performance of feedlot cattle. However, in this study, immunity against BRSV did not appear to protect against the potential synergism between 3MI and BRSV infection, possibly because of the slow rates of gain of cattle included in the study or timing of sample collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…30 This suggests that infection with BRSV and, potentially, other respiratory pathogens lowers the amount of 3MI required to induce AIP. However, it may be postulated that a high concentration of 3MEIN adducts is a necessary, yet not in itself sufficient, cause of feedlot-associated AIP.…”
Section: Discussionmentioning
confidence: 99%
“…30 This suggests that infection with BRSV and, potentially, other respiratory pathogens lowers the amount of 3MI required to induce AIP. However, it may be postulated that a high concentration of 3MEIN adducts is a necessary, yet not in itself sufficient, cause of feedlot-associated AIP.…”
Section: Discussionmentioning
confidence: 99%
“…BRD has been associated with other non-infectious etiologies such as 3-methylindole (Bingham et al , 2000), nutritional interactions and deficiencies (Galyean et al , 1999), production management tools such as hormonal implanting (Munson et al , 2012), sourcing and prior or pre-weaning management (Smith, 1998; Reinhardt et al , 2009; Renter et al , 2013), and genetics (McAllister, 2010). A tremendous amount of work has investigated pathogen interactions related to both clinical and subclinical BRD.…”
mentioning
confidence: 99%
“…In another challenge-exposure study, b 3MI-induced disease was less severe in calves administered aspirin (15.6 g, PO) and α-tocopherol (ie, vitamin E; 1,500 IU, IM) prior to 3MI exposure, compared with disease in control calves or calves administered aspirin or vitamin E prior to 3MI exposure. However, a disease-sparing effect was not detected in a field study 18 in which cattle were administered aspirin (31.2 g, PO) at the time of arrival at a feedlot. The protective effects of aspirin may not have been detected in that study if increases in ruminal generation of 3MI occurred after aspirin-induced inhibition of PHS had waned.…”
mentioning
confidence: 66%
“…Bingham et al 18,19 found that increases in serum concentrations of 3MI at the time of or soon after arrival of cattle at a feedlot were associated with an increased likelihood of treatment because of bovine respiratory disease complex (BRDC). In another study, 17 3MEIN-adduct concentrations in blood samples were increased during the period typically associated with the greatest risk for BRDC, although plasma 3MI concentrations did not exceed basal concentrations.…”
mentioning
confidence: 99%